1995
DOI: 10.1111/j.1467-9493.1995.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracer and Darcy‐based Identification of Subsurface Flow, Bukit Timah Forest, Singapore

Abstract: The spatial distribution of soil hydrological properties and associated flow pathways within a single 0.01 to 10 km2 catchment are usually poorly defined by typical programmes of point‐scale measurements. This is due not only to “measurement uncertainty” caused by instrument error and inadequate spatial sampling but also to “conceptual uncertainty” resulting from a deficiency in the Darcy‐Buckingham‐Richards description of subsurface flow. This study examines these two sources of uncertainty in the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Sherlock et al, 1995Sherlock et al, , 2000. Other research has questioned the accuracy of the Darcy-Richards approach, particularly where natural soil pipes are present, when flow estimates derived from soil-water calculations have not matched measurements of throughflow or streamflow generation (e.g.…”
Section: Field Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Sherlock et al, 1995Sherlock et al, , 2000. Other research has questioned the accuracy of the Darcy-Richards approach, particularly where natural soil pipes are present, when flow estimates derived from soil-water calculations have not matched measurements of throughflow or streamflow generation (e.g.…”
Section: Field Methodologymentioning
confidence: 99%
“…These estimates are, however, evaluated against direct measurements of the relative magnitude and direction of soilwater flow monitored with the use of artificial water tracers. Very few tropical studies have used artificial soil-water tracers (notable exceptions include Bonell et al, 1984;Cabellero et al, 2002;Reichenberger et al, 2002), and even fewer have compared hydrometric predictions against observed tracer paths (Sherlock et al, 1995;Sherlock, 1997).…”
Section: Field Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1a,b shows the locations of the key hillslope hydrology studies (i.e., studies with at least permeability and soil-water measurements) published in the international literature. Six out of ten are on Acrisol-Alisol soils, the dominant soil of Southeast Asia (Sherlock et al 1995;Noguchi et al 1997;Chappell et al 1998;Dykes and Thornes 2000;Schellekens 2000;Kinner and Stallard 2004). A further two studies (Bonell and Gilmour 1978;Elsenbeer and Lack 1996) have results from a mix of Acrisol-Alisol and other soils.…”
Section: Dominant Soil Type In Southeast Asiamentioning
confidence: 99%
“…These hillslope experiments have been conducted at South Creek, Australia (Bonell and Gilmour 1978;Bonell et al 1981Bonell et al , 1983, Reserva Ducke, Brazil (Nortcliff and Thornes 1981), Fazenda Dimona, Brazil (Hodnett et al 1997), Ulu Belalong, Brunei (Dykes and Thornes 2000), Bukit Tarek, Peninsular Malaysia (Noguchi et al 1997), Danum, East Malaysia (Sinun et al1992;Chappell et al 1998Chappell et al , 1999aChappell et al ,b, 2004cChappell and Sherlock 2005), Luquillo, Puerto Rico (Schellekens 2000), Lutz Creek, Panama (Godsey et al 2004;Kinner and Stallard 2004), La Cuenca, Peru (Elsenbeer and Lack 1996), and Bukit Timah, Singapore (Sherlock et al 1995(Sherlock et al , 2000Chappell and Sherlock 2005). Others have attempted to generalise the runoff pathways illustrated in these studies (Chappell and Ternan 1992;Elsenbeer 2001;Bonell 2004), particularly in the upper layers of the ground; we attempt to add to this work.…”
Section: D2mentioning
confidence: 99%